Back Cover: Callipeltosides A, B and C: Total Syntheses and Structural Confirmation (Chem. Eur. J. 38/2015). Issue 38 (2nd September 2015) - Frost, James R.; Pearson, Colin M.; Snaddon, Thomas N.; Booth, Richard A.; Turner, Richard M.; Gold, Johan; Shaw, David M.; Gaunt, Matthew J.; Ley, Steven V.
<x xml:space="preserve">Abstract</x> The synthesis of callipeltosides A, B and C has been achieved in a highly convergent manner. Key to this was the synthesis of the common callipeltoside aglycon by means of an ambitious diastereoselective alkenyl metal addition of the entire bottom fragment to the pyran core, followed by Yamaguchi macrolactonisation. Following this, the endgame was in sight, with each callipeltoside picked off in turn by attachment of the appropriate sugar and unequivocal completion of the series. It's the bullseye! For more information see the Full Paper by S. V. Ley, J. R. Frost, et al. on page 13261 ff.